Incident hand OA is strongly associated with reduced peripheral blood leukocyte telomere length. Issue 12 (December 2018) - McAlindon, T.; Roberts, M.; Driban, J.; Schaefer, L.; Haugen, I.K.; Smith, S.E.; Duryea, J.; Cunha, D.; Blanco, F.; Fernández-Garcia, J.-L.; Eaton, C.
Summary: Objective: To evaluate the relationship of telomere length to the prevalence and incidence of hand osteoarthritis in a longitudinal cohort. Design: We conducted a cross-sectional and longitudinal analysis of data from a subset of participants in the Osteoarthritis Initiative (OAI) recruited between February 2004 and May 2006. 274 individuals were eligible for the study based on availability of both baseline and 48-month hand radiographs and peripheral blood leucocyte telomere length data. Mean telomere length of peripheral blood leukocytes (PBL)s from the DNA samples was determined using a validated quantitative polymerase chain reaction (PCR)-based assay, and hand radiographs were analyzed and graded using the Kellgren–Lawrence scale. Results: In joint –level analyses, prevalent Interphalangeal Joint Osteoarthritis (IPJOA) was significantly associated with PBL telomere length in the baseline sample in unadjusted analyses (RR = 2.84; 95% CI:0.87–9.29) or in models adjusted for age, sex, and body mass index (aRR = 1.10; 95% CI: 0.96–1.27). The association in crude and adjusted analyses appeared slightly stronger with incident IPJOA, especially in the subset with normal hands at baseline (aRR = 1.62; 95% CI: 1.02–2.57). PBL telomere length was also associated with prevalent HOA at baseline (significant in unadjusted analysis: RR = 1.22; 95% CI 1.06–1.42), but not after adjusting for covariates: aRR = 1.12; 95% CI: 0.96–1.30). The magnitude of association was stronger for incident HOA, especially incident symptomatic HOA (aRR = 1.53; 95% CI: 1.09–2.15). Conclusions: In summary, the results of this exploratory analysis are confirmatory of previous work showing a cross-sectional relationship between telomere length and HOA and add to the field by demonstrating an even stronger association with incident IPJOA, both radiographic and symptomatic.